2009
DOI: 10.1111/j.1750-8606.2009.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Should We Care About Adolescents Who Care for Themselves? What We Have Learned and What We Need to Know About Youth in Self‐Care

Abstract: This article provides an overview of existing research on the prevalence and predictors of adolescent self-care and on the consequences associated with it. Self-care, in which the young are left unsupervised during out-of-school hours, is a common experience for millions of American youth, and existing studies suggest that this arrangement may represent a risk for the development of behavior problems. However, the behavior problems associated with self-care depend on both individual and environmental factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…These results are similar to previous research performed during the school year [36][37][38]. Mutunga et al [38] reported significantly higher levels of physical activity and lower levels of energy intake in adolescents with higher socio-economic status compared to their counterparts.…”
Section: Discussionsupporting
confidence: 82%
“…These results are similar to previous research performed during the school year [36][37][38]. Mutunga et al [38] reported significantly higher levels of physical activity and lower levels of energy intake in adolescents with higher socio-economic status compared to their counterparts.…”
Section: Discussionsupporting
confidence: 82%
“…This increase in dual-earner families, and later in single-parent families, led to a child supervision gap between the end of the typical workday and the traditional school day. Simultaneously, the child development study movement was growing (White 2000), and concerns over the safety and development of unsupervised children (i.e., ''latchkey children'') increased (Halpern 2002;Kleiber and Powell 2005;Mahoney and Parente 2009). These concerns were augmented by changes in neighborhood contexts in the early twentieth century, including the growth in urban areas and tenement housing (Halpern 2002).…”
Section: Historical and Current Contextmentioning
confidence: 96%
“…Changes in neighborhood organization and increases in crime, again coupled with the expansion of the child study movement, also increased attention to children who were unsupervised in the after-school hours. Research linking unsupervised care to poor developmental outcomes (e.g., Long and Long 1983;Pettit et al 1997;Mahoney and Parente 2009) augmented the desire for safe after-school care arrangements.…”
Section: Historical and Current Contextmentioning
confidence: 98%
“…In addition, the primary caregiver’s employment status, whether she/he works non-standard hours, single parent status, and perceptions of neighborhood safety are included as controls because these factors have been shown to predict the types of out-of-school experiences that youth have (e.g., Mahoney et al, 2009; Shann, 2001; U.S. Census Bureau, 2009) and are closely tied to other known predictors of child obesity (e.g., household income).…”
Section: Expected Findingsmentioning
confidence: 99%